Portraying Islam and the West : in Tzvetan Todorov’s The Fear of Barbarians: Beyond the Clash of Civilizations - Tijani Boulaouali (UIN Sunan Gunung Djati Bandung, 2023)
This review deals with the relationship between Islam and the West from the point of view of the Bulgarian-French philosopher Tzvetan Todorov, especially in his book the Fear of Barbarians. Some issues have been discussed. Firstly, the term barbarism or savagery is defined and compared with the concept civilization. Secondly, attention is paid to Todorov's historical criticism of a number of Western concepts and postulates that they are circulating in politics and the media. Finally, some negative stereotypes about Islam and Muslims, that Todorov has criticised and corrected, have been highlighted in this article.